United Republic of Tanzania - Public Expenditure Review 2011 - World Bank (Washington, DC, 2013)
The 2011 Public Expenditure Review (PER) is divided into two parts. The first describes recent developments in fiscal policy, with a particular focus on the adjustment announced in November 2011 as well as short and long term prospects. The second part assesses government performance in the health sector, which accounts for about 10 percent of the total budget. The objectives of the budget analysis chapter are to: 1) document fiscal and macro developments since November 2011, after the government made adjustments to the budget under the International Monetary Fund (IMF) Policy Support Instrument (PSI). Government reduced the fiscal deficit in the budget to approximately 6.6 percent of Gross Domestic Product (GDP) from approximately 8.0 percent of GDP in the initially approved budget for 2011/12. 2) Take stock of budget execution in 2010/11 and strategic budget allocation in 2011/12 in relation to Government strategic objectives of economic growth and poverty reduction as envisaged in MKUKUTA (Mpango wa Kukuza Uchumi na Kupunguza Umaskini Tanzania-Tanzania's National Strategy for Growth and Reduction of Poverty) and Five Year Development Plan (FYDP). 3) Highlight a number of priorities that Government needs to take into account in formulating its fiscal policy both in the short and longer terms. In 2011, the recurring domestic energy crisis negatively affected the level of private sector activities. The Bank of Tanzania's tighter monetary policy is aimed at reducing the inflation rate, which reached 16.8 percent and 19.8 percent in September and December 2011, respectively.